Aortic regurgitation severity after transcatheter aortic valve implantation is underestimated by echocardiography compared with MRI. Issue 24 (24th July 2014) - Orwat, Stefan; Diller, Gerhard-Paul; Kaleschke, Gerrit; Kerckhoff, Gregor; Kempny, Aleksander; Radke, Robert M; Buerke, Boris; Burg, Matthias; Schülke, Christoph; Baumgartner, Helmut
Abstract : Objective: Aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) is associated with a poor clinical outcome and its assessment therefore crucial. Quantification of AR by transthoracic echocardiography (TTE), however, remains challenging in this setting. The present study used quantitative flow measurement by cardiac MRI (CMR) with calculation of regurgitant fraction (RF) for the assessment of AR and compared the results with TTE. Methods and results: We included 65 patients with a mean age of 82.2±8.1 years (38 women) who underwent successful TAVI with Edwards SAPIEN valves (52 transfemoral, 13 transapical). The postinterventional degree of AR was assessed by CMR and by TTE. There was agreement between CMR and TTE with regards to the absence of severe AR. However, TTE significantly underestimated the presence of moderate AR classifying it to be mild in 38 and moderate in only 5 patients, whereas CMR found mild AR in 23 and moderate in 16 patients. Overall, there was only fair agreement between CMR and TTE regarding the grading of AR with a weighted κ of 0.33. The rate of detection of TTE for more than mild AR was only 19%. Conclusions: Using CMR for the quantification of AR in a sizeable group of TAVI patients, we demonstrate a strong tendency of TTE to underestimate AR compared with CMR. Since higher AR severity on echocardiography has been associated with worse patient outcome, the potential incremental prognostic value of CMR should be studied prospectively in this setting.